STUDENTS’ INTEREST IN LEARNING ENGLISH DURING NEW NORMAL ERA OF COVID-19 PANDEMIC - Andi Alfiana; Maemuna Muhayyang; Amirullah Abduh (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This research aims to find out how students' interest in learning English during the new normal era of the covid 19 pandemic at the State University of Makassar was conducted on August 2022. This research is a quantitative descriptive study. The method used in this research is a survey method. The collecting data using a questionnaire in the form of a Google form. The sample in this research was 40 students using a random sampling technique from the fifth semester of the English Department. The questionnaire distributed consisted of 25 statements with four indicators namely feeling happy, student involvement, interest and student attention. Based on the results of the research showed that the indicators of the highest indicator are the 3rd indicator, namely an interest in the good category and the lowest is the 1st indicator, namely feeling happy with the good category. Students' interest in learning of the interest indicator was included in the good category. Because of the students’ interest in the fifth semester in learning English is still relatively high for learning even though the new normal period of learning at that time through the application that the lecturer used was WhatsApp or Zoom, so whatever happens, they have to keep going & studied with friends or looking for references on the internet to understand the English lessons given because it is also their obligation & can support the score of their learning outcomes later. It can be inferred from the research's findings that the interest of fifth-semester students majoring in English at the State University of Makassar in learning English during the new normal era for the Academic Year 2021/2022 is in a good category.